Modular Version of The Total Vertex Irregularity Strength for The Generalized Petersen Graph - Nasution, Dina Khairani; Susilawati (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2025)
Let be a graph. A labeling graph is a maps function of the set of vertices and/or edges of , to the set of positive integers. A total modular labeling is said to be a -modular total irregular labeling of the vertices of , if for every two distinct vertices and in , the modular weights are different, and belong to the set of integers . The minimum such that the graph has a - modular total irregular labeling is called the modular total vertex irregularity strength and denoted by . In this paper, we study about the modular total vertex irregularity strength for the generalized Petersen graph . The result show that the exact value is .